The Role of Transformers in Electric Power Engineering - Maxamadov Muhammadali (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the importance of transformers in the electric power system, their operating principles, and their role in the transmission and distribution of electrical energy. The operation of transformers based on electromagnetic induction, their functions of increasing and decreasing voltage, and their galvanic isolation properties are discussed. The main types of transformers, including power transformers, distribution transformers, and instrument transformers, as well as their fields of application, are also examined. The article provides a detailed explanation of transformer efficiency, energy losses, cooling systems, and the impact of insulation conditions on operational reliability. Furthermore, modern energy-saving technologies, methods for reducing magnetic core losses, and innovative solutions for improving efficiency are analyzed. The research findings demonstrate the significant role of transformers in ensuring energy efficiency and maintaining uninterrupted power supply within electric power systems.